The lncRNA ALMS1‐IT1 may promote malignant progression of lung adenocarcinoma via AVL9‐mediated activation of the cyclin‐dependent kinase pathway - Tian Luan; Tian‐Ye Zhang; Zhong‐Hua Lv; Bi‐Xi Guan; Jian‐Yu Xu; Jian Li; Ming‐Xu Li; Song‐Liu Hu (FEBS Open Bio, 2021)
Lung adenocarcinoma (LUAD) is the primary epithelial tumor of the lung. The lack of clinical symptoms and specific molecular diagnostic indicators during the early stages of LUAD mean that the disease may not be detected until late stages, and the 5‐year survival rate is only approximately 15%. Long non‐coding RNA ALMS1 intronic script 1 (ALMS1‐IT1) was previously reported to be correlated with the poor prognosis of head and neck squamous cell carcinoma patients. Here, we investigated whether ALMS1‐IT1 has prognostic potential for LUAD. Bioinformatics analyses were performed to examine the expression and prognostic value of ALMS1 and AVL9 (for which gene expression is positively correlated with ALMS1‐IT1 expression in LUAD) in LUAD based on TCGA and Oncomine databases. We report that ALMS1‐IT1 and AVL9 were both highly expressed in LUAD and correlated with poor outcomes in LUAD patients. Of note, the prognosis of LUAD patients with low expression of both ALMS1‐IT1 and AVL9 was superior to that of other patients. Furthermore, the proliferation, migration and invasion of LUAD cells were decreased in cells lacking ALMS1‐IT1, and this decrease could be almost completely reversed through overexpression of AVL9. Gene set enrichment analysis revealed that expression of genes related to the cell cycle pathway is closely related to both the high expression of ALMS1‐IT1 and AVL9 in LUAD. Finally, up‐regulation of ALMS1‐IT1 can activate the cyclin‐dependent kinase pathway, whereas absence of AVL9 can reverse this activation, as shown by western blotting. In summary, ALMS1‐IT1/AVL9 may promote the malignant progression of LUAD, at least in part by regulating the cyclin‐dependent kinase pathway.